2020
DOI: 10.3390/vaccines8020287
|View full text |Cite
|
Sign up to set email alerts
|

Schmallenberg Virus: To Vaccinate, or Not to Vaccinate?

Abstract: Schmallenberg virus (SBV), a teratogenic orthobunyavirus that infects predominantly ruminants, emerged in 2011 in Central Europe, spread rapidly throughout the continent, and subsequently established an endemic status with re-circulations to a larger extent every 2 to 3 years. Hence, it represents a constant threat to the continent’s ruminant population when no effective countermeasures are implemented. Here, we discuss potential preventive measures to protect from Schmallenberg disease. Previous experiences w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 109 publications
0
7
0
1
Order By: Relevance
“…The prevention of infections with simbuviruses or BTV and, along with it, the prevention of clinical disease, abortion, fetal malformation or potential reassortment events is complicated by the transmission mode, as insect-transmitted viruses are harder to control by means other than vaccination than are pathogens directly transmitted from animal to animal. As an example, European experiences during the BTV-8 outbreak in 2006/2007 have demonstrated that vaccination can play a major role in reducing virus circulation or even in eradicating a vector-transmitted disease from a given region [66,67], while SBV, for which no vaccination campaign is in place, is endemic in Central Europe since its initial emergence about 10 years ago [61,68]. In contrast, BVDV has been successfully eradicated from several countries without vaccination after the implementation of control programs that are based on systematic control, the identification and rapid removal of infected animals, movement restrictions and further biosecurity measures [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of infections with simbuviruses or BTV and, along with it, the prevention of clinical disease, abortion, fetal malformation or potential reassortment events is complicated by the transmission mode, as insect-transmitted viruses are harder to control by means other than vaccination than are pathogens directly transmitted from animal to animal. As an example, European experiences during the BTV-8 outbreak in 2006/2007 have demonstrated that vaccination can play a major role in reducing virus circulation or even in eradicating a vector-transmitted disease from a given region [66,67], while SBV, for which no vaccination campaign is in place, is endemic in Central Europe since its initial emergence about 10 years ago [61,68]. In contrast, BVDV has been successfully eradicated from several countries without vaccination after the implementation of control programs that are based on systematic control, the identification and rapid removal of infected animals, movement restrictions and further biosecurity measures [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Для предотвращения новых вспышек и снижения риска возникновения новых очагов инфекции может применяться вакцинация всего восприимчивого поголовья. Более рентабельной стратегией может быть вакцинация самок животных всех восприимчивых видов до наступления репродуктивного возраста [45].…”
Section: основная частьunclassified
“…La Crosse virus (LACV) is the most common neuroinvasive arboviral infection in children (Boutzoukas et al, 2023) in the United States (Vahey et al, 2021) and serves as a study model for other neuroinvasive orthobunyaviruses such as Jamestown Canyon orthobunyavirus (JCV) and Snowshoe hare orthobunyavirus (SSHV) in the USA and Canada (Evans & Peterson, 2021), Tahyna orthobunyavirus (TAHV), which is widely distributed throughout Europe, Africa and Asia, and Inkoo orthobunyavirus (INKV), which is found in Scandinavia (Lwande et al, 2017;Vapalahti et al, 1996). Other animal-infecting orthobunyaviruses include Schmallenberg virus (SBV) and Akabane virus, which severely affect ruminants (Wernike & Beer, 2017;Yanase et al, 2020). Reports of the newly identified Cristoli orthobunyavirus and the emergence of Umbre orthobunyavirus as agents responsible for fatal encephalitis (Rodriguez et al, 2020;Pe ´rot et al, 2021) stress the importance and necesssity of monitoring the impact of orthobunyaviruses on human health and activities.…”
Section: Introductionmentioning
confidence: 99%